?UTILIZATION OF RAPESEED MEAL/CAKE IN POULTRY FEED I.EFFECT OF INCORPO- RATING 10% RAPESEED CAKE IN POULTRY DIET ON THE GROWTH AND LAYING PERFORMANCE OF BROWN-EGG-LAYER (TETRA SL) (Biological Sciences - PJSIR, 1998)
Fifteen days old 100chicks were divided into two groups. One group was maintained on standard diet, while the other group was fed on the diet containing 10% rapeseed cake. During 34 weeks of the experiment, rapeseed group was studied for liveability,feed consumption, laying performance andegg quality in comparison with the standard group. No adverse effect was observed rather beneficial effect was observed on the growth and laying performance at this level. Feed consumption for the period of first 6 weeks was 857g chick" for standard group and 918g chick" for rapeseed cake group. Live weight after 20 weeks was 1478.88g pullet:' for standard group and J 503.07 g puller' for rapeseed cake group. Laying record of seven weeks showed significant increase (p